Public perception of religion and worldviews education - Wright, Kathryn (2022)
This article is based on work undertaken by Culham St Gabriel’s Trust, a charitable organisation in the UK which is committed to the development of ‘a broad-based, critical and reflective education in religion and worldviews contributing to a well-informed, respectful and open society.’ The article highlights the results of a survey by the Trust in June 2021 which aimed to establish a baseline regarding the public perception of religious education (RE) in schools, and wider views around religious-, spirituality-, belief- and worldview-literacy. The Trust plans to use this baseline to measure the impact of interventions and campaigns through its own programmes and grant-funded projects over the coming years. Previous surveys have suggested that the UK population has negative perceptions of religious education; however, these new results indicate that the majority of those surveyed have a positive view of the subject and value the importance of religious and belief literacy in a range of contexts. The article sets out the key findings of the survey; it also includes some personal reflections and analysis, as well as reference to media engagement. Alignment of the results with pupil perspectives is considered, and finally conclusions are drawn about potential next steps and use of the findings in programme and policy development.
Keywords: Spirituality; campaign; Public Perception; Worldviews; Religion